12th Computational Fluid Dynamics Conference 1995
DOI: 10.2514/6.1995-1740
|View full text |Cite
|
Sign up to set email alerts
|

Implicit/multigrid algorithms for incompressible turbulent flows on unstructured grids

Abstract: SummaryAn implicit code for computing inviscid and viscous incompressible flows on unstructured grids is described. The foundation of the code is a backward Euler time discretization for which the linear system is approximately solved at each time step with either a point implicit method or a preconditioned Generalized Minimal Residual (GMRES) technique. For the GMRES calculations, several techniques are investigated for forming the matrix-vector product. Convergence acceleration is achieved through a multigri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
106
0

Year Published

1999
1999
2015
2015

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(108 citation statements)
references
References 24 publications
2
106
0
Order By: Relevance
“…In this section, the flow solvers FUN2D and FUN3D [104,105] used for this work are described in detail. These codes were chosen because our studies were conducted for NASA Langley, so close cooperation was facilitated.…”
Section: Flow Solvermentioning
confidence: 99%
“…In this section, the flow solvers FUN2D and FUN3D [104,105] used for this work are described in detail. These codes were chosen because our studies were conducted for NASA Langley, so close cooperation was facilitated.…”
Section: Flow Solvermentioning
confidence: 99%
“…FUN3D, [3][4][5][6][7][8] an unstructured CFD code developed at NASA Langley, provides extensive adjoint-based capabilities for design optimization for many design parameters. The ultimate long-term goal of the research conducted by the authors is to develop an adjoint formulation for LASTRAC and integrate it with the adjoined-based capabilities of FUN3D to enable design optimization that directly maximizes the laminar-flow regions.…”
Section: Introductionmentioning
confidence: 99%
“…The refinement factor "r" is defined as "r=h k+1 /h k " where "h k " and "h k+1 " are successive values of parameter "h". More specifically if h 1 , h 2 and h 3 are three levels of parameter "h" such that r 12 =h 2 /h 1 =2 and r 23 =h 3 /h 2 =2 and the corresponding numerical solutions for "Φ" are 1  , 2  , 3  then we can write the following equations:…”
Section: Temporal and Spatial Accuracymentioning
confidence: 99%
“…The symbol "" means that the various quantities are evaluated with algebraic averaging of " L Q ", " R Q ". In two dimensions we used the eigensystem of Roe's matrix that was reported by Anderson et al (1995), while in three dimensions we used the eigensystem reported by Shin (2001). The left and right state vectors are evaluated by a third-order accurate upwind interpolation scheme along edge "ij" (Tai et al, 2005):…”
Section: Inviscid Fluxmentioning
confidence: 99%